The update and ecological status of the flora of the Belezma National Park, Algeria - AMIRA BENCHOUALA; FARID BEKDOUCH; ABDLEKRIM SI BACHIR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Benchouala A, Bekdouche F, Si Bachir A. 2023. The update and ecological status of the flora of the Belezma National Park, Algeria. Biodiversitas 24: 6134-6150. The establishment of national parks and nature-protected areas helps to conserve biodiversity. The conservation and enhancement of the floristic diversity of the Belezma National Park (BNP), Algeria which is also designated as biosphere reserve, require precise knowledge of its flora. To that end, the inventory conducted at BNP at the level of forest massifs, preforests, and mountain grasslands enabled us to identify 562 taxa belonging to 342 genera and 93 families, with a predominance of Asteraceae, Poaceae, and Fabaceae. Based on biological spectrum, hemicryptophytes outnumbers other life forms by 44.4%. Zoochory is the most common distribution mode among inventoried species (44.3%). The Mediterranean type dominates the chronological spectrum with proportion of 45.9%. Endemism is represented by 53 species (9.4% of the total flora). According to executive decree No. 12-03 of January 4, 2012, the BNP flora consists of 196 rare species, including 34 endemic species and 26 threatened and protected ones in Algeria. Based on our results, it has been possible to constitute a database of the BNP flora, useful for its protection.